COMMUNITY RESPONSE IN SUPPORTING THE SMART CITY PROGRAM IN DENPASAR CITY - Shania Natasya; I.G.A.AG Dewi Sucitawathi P (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
The concept of Smart City is a concept currently adopted to describe the conditions of information technology-based governance. Public services must adapt to change, and must be able to apply the principles of Good Governance. Community response is one measure of the success of policies / programs created by the government, such as the Denpasar Smart City program. This study aims to determine the response of the community in supporting the Smart City program in the city of Denpasar. The research method used was descriptive qualitative, and data collection techniques used were in the form of interviews, observation, study of literature and qualitative documents, qualitative audio and visual. The results showed that the implementation of Smart City policies in order to realize Smart Government in Denpasar City, in general, had a positive impact on target groups. The context of implementation of the Smart City program in Denpasar showed poor conditions, while the content of policy showed good conditions, and there was a positive public response to the application of the Denpasar Smart City program that emphasized the principles of transparency and public openness.